ANALISA PENGARUH BENTUK PIPA KAPILER DAN KECEPATAN UDARA EVAPORATOR TERHADAP EFEKTIVITAS MESIN PENDINGIN AIR COOLER 1PK - Priyo Utomo, Gatut; Santoso, Teguh (MEKANIKA: Jurnal Teknik Mesin, 2017)
Air cooling machines has become a secondary requirement in major cities. This is because the air temperature continues to rise each year. Cooling machine has the central point in use they can be used as air-conditioning, food preservatives, and others - others. The impact that often occurs in using of cooling machine is continuously increasing the risk of damage to the cooler. Damage often occurs in the compressor of the cooling machine. The compressor itself is the heart of the cooling system. The cause damage to the compressor is usually due to inhibition of the capillary tube crust. In this study, the writer uses a shape variation of the capillary tube like spirals, triangles, rectangles and evaporator air velocity of 2.5 m/s, 4 m/s, 5 m/s, but with the same diameter capillary tube which is 0,54 mm. Based on the results of research that is conducted the best to form a capillary tube is evaporator spiral with air speed of 4 m/s, it is marked by the largest price of COP 10.5. This is due to compression levels fell to 18.6%, the effectiveness of the cooling machine would rise. Keywords: Air velocity, COP (Coefficient of Performance), effectiveness of the machine, Shape of capillary tube